The responsiveness of remittances to the oil price: the case of the GCC - George S. Naufal; Ali Termos (Institute for the Study of Labor (IZA), 2009)
We investigate the responsiveness of remittances from the Gulf Cooperation Council (GCC) countries to the changes in the price of crude oil. Most of the GCC countries rank in the top 20 remitting countries in the world. We find that oil price elasticity of remittances is around 0.4. While most studies have examined the impact of remittances on the real economic activities in the receiving countries, this study emphasises the impact of remittances on the remitting countries. We examine various policy implications with regard to macroeconomic shocks, monetary policy and fiscal policy of the GCC countries.
urn:nbn:de:101:1-2009082062
Keywords: F24; P22; N15; 330; Elasticity; remittances; oil price; GCC; Rücküberweisung (Migranten); Erdölpreis; Elastizität; Arabische Golf-Staaten